The Safety of Areca Seed Ethanolic Extract as Potential Chemopreventive Agent is Proven by Acute Toxicity Test - Sri Handayani; Riris Istighfari Jenie; Ratna Asmah Susidarti (Indonesian Journal of Cancer Chemoprevention, 2012)
Areca (Areca catechu L.) seeds ethanolic extract (AE) exhibits antiproliferative activity and induces apoptosis on T47D and MCF-7 cells. This study aimed to verify AE safety using acute toxicity test to support its development as chemopreventive agent. Male Sprague Dawley Rat (Rattus norvegicus) age 8 weeks divided into five groups, one group of control treated with 0.5% CMC-Na only and four groups for treatment. Single dose in oral administration was done to test animal with various dose of AE starts from lowest dose to highest dose expected toxic to all of test animal (0.1; 0.72; 5.36 and 10 gram/kgBW). Observation was done during 24 hours and continued for 14 days. The observation criteria were toxic symptoms, appearance and mechanism of toxic effect and pathology of vital organ. Histopathology analysis of some vital organs was done with Haematoxyllin&Eosin (H&E) staining. Toxic effect did not appear either on treatment groups or control group. Treatment of single dose of areca ethanolic extract, even in highest dose, did not cause the death of the animals. Therefore, observation extended to 14 days and terminated by necroption of the animals. All of groups did not show histopathological alterations in microscopic observation. Category of the potential toxicity of AE is practically non-toxic, ie 10 g/kgBW. The result shows the safety of areca seed ethanolic extract which is important for its development as chemopreventive agent.Keywords: Areca catechu, acute toxicity, rat